Assessment of risk factors for congenital heart disease through prenatal fetal echocardiography and the correlation with postnatal diagnoses - Kaan Yıldız; Yunus Sezer Bayam; Hüseyin Bardak; Yağmur Damla Akçura; Hazer Erçan Bozyer; Veysel Çeliktepe; Halise Zeynep Genç; Mustafa Kır; Onur Taşcı; Cemile Kübra Zeybek; Nurettin Ünal (Trends in Pediatrics)
Background: Congenital Heart Disease (CHD) constitutes a significant cause of morbidity and mortality in newborns. Identifying CHD prenatally and understanding associated risk factors can aid in early diagnosis, intervention, and postnatal management. This study aims to assess risk factors for CHD using prenatal fetal echocardiography (FE) and investigate their correlation with postnatal diagnoses.